The effect of stimulation therapy and donepezil on cognitive function in Alzheimer's disease. A community based RCT with a two-by-two factorial design - Andersen, Fred; Viitanen, Matti; Halvorsen, Dag; Straume, Bjørn; Wilsgaard, Tom; Engstad, Torgeir (BMC Neurology, 2012)
This article is part of Fred Andersen's doctoral thesis. Available in Munin at http://hdl.handle.net/10037/3669 Progressive neurodegeneration in Alzheimer’s disease (AD) induces cognitive deterioration, and there is controversy regarding the optimal treatment strategy in early AD. Stimulation therapy, including physical exercise and cholinesterase inhibitors are both reported to postpone cognitive deterioration in separate studies. We aimed to study the effect of stimulation therapy and the additional effect of donepezil on cognitive function in early AD. Design: A two-by-two factorial trial comprising stimulation therapy for one year compared to standard care to which a randomized double-blinded placebo controlled trial with donepezil was added. Setting: Nine rural municipalities in Northern Norway. Participants: 187 participants 65 years and older with a recent diagnosis of mild or moderate AD were included in the study of which 146 completed a one-year follow-up. INTERVENTIONS: In five municipalities the participants received stimulation therapy whereas participants in four received standard care. All participants were randomised double-blindly to donepezil or placebo and tested with three different cognitive tests four times during the one-year study period. Main outcome: Changes in MMSE sum score. Secondary outcome: Changes in ADAS-Cog and Clock Drawing Test. MMSE scores remained unchanged amongst AD participants receiving stimulation therapy and those receiving standard care. The results were consistent for ADAS-Cog and Clock Drawing Test. No time trend differences were found during one-year follow-up between groups receiving stimulation therapy versus standard care or between donepezil versus placebo. In rural AD patients non-pharmacological and pharmacological therapy did not improve outcome compared with standard care but all groups retained cognitive function during one year follow-up. Other studies are needed to confirm these results.